(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
Steel sandwich structures with honeycomb and corrugated cellular cores have demonstrated the capability of supporting significant static bending loads while also enabling effective mitigation of impulse loads, the main objectives to use these structures is weight reduction and isolate or reduce the deflection and stress. This research aims to study the effect of dynamic load on the dynamic properties of various types of sandwich cores then find the best model that withstand high stresses and dissipate loads with less mass was possible. The studied model of sandwich is of dimensions (500x500x100) mm with five cells. Four types of steel sandwich plate (SSP) finite element models of various core types have been created: (1) triangle corrugated core, (2) trapezoid corrugated core, (3) square honeycomb and (4) out-of plane hexagonal honeycomb, the mass of various types was constant with value of 13.75 kg. The SSP types were compared by using ANSYS (15.0) APDL software.The finite element models are examined under the effect of transient concentrated stepped load of (350N) during 10ms. The time history response showed that the minimum von-Mises stress and minimum deflection occur at triangle corrugated SSP with values of stress (12.5Mpa) and deflection (3.8 ), but in energy absorption the square honeycomb is the best type with reduction of stress (99.65%) and reduction of deflection of (98.95%).